Biocompatibility of cardiopulmonary bypass circuit with new polymer Senko E-Ternal CoatingTM. (October 2015) - Fukui, T; Nishida, H; Takanashi, S
Objective: The aim of this study was to compare the biocompatibility of a new Senko E-Ternal coating (SEC) for cardiopulmonary bypass (CPB) circuits with the well-established poly-2-methoxyethyl acrylate (PMEA) coating. Methods: Forty patients undergoing aortic valve replacement were randomly assigned to either an SEC-coated group (n = 20) or a PMEA-coated group (n = 20). Clinical data and the following markers were analyzed: platelet count, platelet factor (PF) 4, fibrinogen, fibrinogen degradation products (FDPs), antithrombin III (AT III), thrombin-antithrombin complex (TAT), plasminogen, complement hemolytic activity (CH50), complement 3 (C3) and interleukin-6 (IL-6). Blood samples were obtained at five time points in both groups. Results: CPB time, aortic cross-clamp time and blood loss and transfusion were similar in both groups. There were no significant differences between the groups in terms of platelet count, PF4 and all coagulation and fibrinolytic parameters (FDP, AT III, TAT, and plasminogen) at any time points. Inflammatory markers (CH50, C3 and IL-6) were also similar in both groups at all time points. Conclusions: The SEC-coated circuit demonstrated equivalent biocompatibility to the PMEA-coated circuit. SEC-coated circuits are, therefore, favorably comparable to PMEA-coated circuits for clinical use in CPB.